The effect of probiotics on respiratory tract infection with special emphasis on COVID-19: Systemic review 2010–20. (April 2021) - Darbandi, Atieh; Asadi, Arezoo; Ghanavati, Roya; Afifirad, Roghayeh; Darb Emamie, Amir; kakanj, Maryam; Talebi, Malihe
Highlights: Probiotics may reduce viral titer, and respiratory infection incidence and duration. Probiotics may increase cytokine plasma levels, vaccine effect and quality of life. Trials required on pro/synbiotics mechanisms to optimize therapy effect and safety. Abstract: To evaluate the effects of probiotics on respiratory tract infection (RTI) a systematic review of randomized controlled trials (RCTs) from January 2010 to January 2020 was conducted. The PubMed, Google Scholar, Embase, Scopus, Clinicaltrials.gov, and International Clinical Trials Registry Platform databases were systematically searched for the following keywords: respiratory tract infection, probiotics, viral infection, COVID-19, and clinical trial. A total of 27 clinical trials conducted on 9433 patients with RTI plus 10 ongoing clinical studies of probiotics intervention in Coronavirus disease 2019 (COVID-19) were reviewed. The review looked at the potency of probiotics for the hindrance and/or treatment of RTI diseases, this may also apply to COVID-19. The review found that probiotics could significantly increase the plasma levels of cytokines, the effect of influenza vaccine and quality of life, as well as reducing the titer of viruses and the incidence and duration of respiratory infections. These antiviral and immune-modulating activities and their ability to stimulate interferon production recommend the use of probiotics as an adjunctive therapy to prevent COVID-19. Based on this extensive review of RCTs we suggest that probiotics are a rational complementary treatment for RTI diseases and a viable option to support faster recovery.